Kritische Edition der sahidischen Version des Johannesevangeliums Text und Dokumentation - Förster, Hans; Sänger-Böhm, Kerstin; Schulz, Matthias H. O. (Arbeiten zur neutestamentlichen Textforschung, 2021)
Sahidic is one of the most important Coptic literary dialects. A modern, critical edition of the Sahidic translation of the New Testament has long been missing from the academic field. A research project funded by the FWF Austrian Science Fund (P29315) has now made it possible to produce a critical edition of the Sahidic Gospel of John, based on 172 different preserved manuscripts, most of them fragments.